Bel canto [videorecording (DVD)] - Moore, Julianne; Watanabe, Ken, 1959-; Lambert, Christopher, 1957-; Koch, Sebastian, 1962-; Pachett, Ann (Screen Media Films, 2018)
Roxanne Coss becomes trapped in a hostage situation when she's invited to perform at a lavish party for a wealthy industrialist in South America. As a lengthy standoff ensues, hostages and captors form unexpected bonds as they overcome their differences to find their shared humanity.